RETARDATION OF PROGRESSION OF CHRONIC KIDNEY DISEASE THROUGH PHARMACOLOGICAL INTERVENTIONS - K, Tirumalesh; Nimmanapalli, Harini Devi; P M, Rajitha P M; G, Divya; N, Mahesh Kalyan; Vishnubotla, Siva Kumar (Journal of Biomedical and Pharmaceutical Research, 2018)
Abstract: Objective: Chronic Kidney Disease (CKD) patients have multiple co-morbidities and complications, and are prescribed with large number of medications. Studies on therapeutic strategies to slow the chronic kidney disease progression in India are limited. Aim of the study: The present study was undertaken to evaluate retardation of progression of Chronic Kidney Disease through pharmacological interventions. Materials and Methods: This was a retrospective study conducted during 6 months period from August 2017 to January 2018 on 180 patients diagnosed with CKD Results: The present study found the mitigating effect of the pharmacotherapy on indicator parameters in reducing the progression of CKD for the DM-CKD and Non DM-CKD groups Conclusion: The findings of present study conclude that pharmacological interventions of Seven indicator parameters in the management Diabetes mellitus , Anaemia, Hypertension, Hyperphosphatemia, Hyperuricemia, proteinuria and Metabolic acidosis was beneficial to slow the progression of renal disease in DM-CKD and Non DM-CKD patients. Key words: Chronic kidney disease, pharmacological, intervention, Diabetes mellitus, progression.